THE IMPORTANCE OF ECOLOGICAL CONTEXTS IN STEAM EDUCATION IN 7TH GRADE PHYSICS - Otarbaev, Amangeldi Edilbekovich (SCIENCE and SOCIETY, 2026)
This article details the scientific and methodological aspects of using ecological contexts based on STEAM education in 7th-grade physics lessons in general education schools. The study examines effective methods for increasing students' interest in the subject, connecting theoretical knowledge with practice, and forming ecological culture through integrating environmental problems with the STEAM approach. The article also analyzes environmentally oriented STEAM projects, lesson organization methods, expected pedagogical outcomes through mini-projects and practical assignments, and provides scientific and methodological recommendations.
Keywords: STEAM education; environmental context; physics; 7th grade; interdisciplinary integration; environmental culture